Topographic evaluation of fifth-generation GOCE gravity field models – globally and regionally - Hirt, Christian; Rexer, M.; Claessens, Sten (2015)
ESA (European Space Agency) has released a series of new-generation Earth gravity field models computed from gradiometry and GPS observations carried out aboard the GOCE (Gravity field and Ocean Circulation Explorer) satellite. In order to assess the quality of the new GOCE gravity fields, the sensitivity of satellite gravimetry to the gravitational attraction of the topographic masses can be exploited. This study uses topographic mass models to evaluate five generations of GOCE gravity models, both globally and regionally. As model representing Earth’s topography, ice-sheet and waterbody masses we use the new RET2014 rock-equivalent topography model by Curtin University (Perth). The gravitational potential of the RET2014 model is computed in spherical harmonics and in ellipsoidal approximation (ellipsoidal topographic potential, cf. Claessens and Hirt 2013, JGR Solid Earth, 118, 5991). We compare gravity from GOCE and from the RET2014 topography, whereby similar signal characteristics are taken as a sign of quality for the GOCE gravity fields.Our topographic evaluation shows a steadily improved agreement of the five model generations with topographyimplied gravity, and increase in GOCE model resolution. For the fifth-generation GOCE gravity fields, full resolution is indicated to harmonic degree ~220 (90 km scales), and partially resolved gravity features are found to degree ~270 (time-wise approach, TIM) and degree ~290-300 (direct approach, DIR), As such, the 5th-generation GOCE models capture parts of the gravity field signal down to ~70 km spatial scales. This is a very significant improvement in satellite-only static gravity field knowledge compared to the pre-GOCE-era. Our comparisons show that models from the DIR approach improved relative to those from the TIM approach from the 2nd to the 5th generation, with DIR offering the best short-scale performance (from degree 240 and beyond). Considering the unprecedented gravity field resolution achieved, the GOCE gravity field mission performed beyond the expectations. The GOCE gravity fields will serve as a de-facto-standard in a range of applications encompassing geodesy, geophysics and oceanography.